The First World War in the Interwar French Novel. Montherlant, Cocteau, Radiguet. - Adinolfi, Pierangela (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
The First World War in the Interwar French Novel. Montherlant, Cocteau, Radiguet. The Great War left a strong mark on the French novels of the interwar period, as those years exacerbated the subjective manifestations and the objective consequences of human uneasiness. The turmoil of personal conscience led to the creation of characters that flaunt an inextinguishable will for power, as can be seen in the works of Montherlant and Malraux. The narratives revolve around the life courses of exemplar characters that try to compensate for the restlessness of the self by searching for the exaltation and freedom of the individual. The space of the novel acquires mythical and symbolic values. The novel’s time is concentrated in magical moments. The characters become emblematic or allegoric figures. In this context, the transfiguration of the war experience is the underlying theme of Songe by Henry de Montherlant, Thomas l’imposteur by Jean Cocteau and Diable au corps by Raymond Radiguet. These novels’ heroes are the young protagonists of an initiation to life that occurs between the disorder of History and the aspiration to individual freedom.